Kelayakan Video Pembelajaran Berbasis Platform Youtube pada Materi Bilangan Pecahan di Kelas IV Sekolah Dasar Negeri 05 Pontianak Kota - Claudia Titin Tutu Sari; Bistari Bistari; Siti Halidjah (Departement of Mathematics Education, 2023)
This study aims to describe the appropriateness of learning videos based on the YouTube platform on fraction material in grade IV and student responses to the use of teaching videos based on the YouTube platform. This study uses qualitative research with descriptive methods. Data analysis techniques are data collection, reduction, presentation, and verification/conclusion. Testing the validity of the data used a credibility test with a data-checking technique, namely the triangulation technique. The average video feasibility in the content aspect is categorized as feasible with a percentage of 87.7%; the presentation aspect is categorized as proper with a ratio of 91.9%; the language aspect is categorized as appropriate with a balance of 94.7%; Graphic aspects are classified as very feasible with a percentage of 87.3%. From these four aspects, it is stated that it can be used as a learning reference. The average student response in the cognitive aspect is 75.9%, the affective aspect 72.8%, conative aspect 73%.